Individual values of GenZ in managing their Internet Privacy: a decision analytic assessment - Dhillon, Simran Kaur (2022)
A nossa investigação coloca a importância dos valores individuais como o centro de qualquer discussão sobre questões de privacidade. Os valores têm um papel essencial no discurso científico. Notamos que o conceito de valores é um dos poucos discutidos e utilizados em várias disciplinas das ciências sociais. Para isso, nesta investigação, apresentamos objetivos baseados em valores para a privacidade na Internet da GenZ. Os objetivos são classificados em duas categorias - os objetivos fundamentais e os meios para os atingir. Em síntese, os nossos seis objetivos fundamentais orientam a gestão das questões de privacidade da Internet da GenZ. Os objetivos são: Aumentar a confiança nas interações online; Maximizar a responsabilidade dos detentores de dados; Maximizar o direito à privacidade; Maximizar a capacidade individual de gerir o controlo da privacidade; Maximizar a percepção da funcionalidade da plataforma; Garantir que os dados pessoais não são alterados. Coletivamente, os objetivos fundamentais e de meios são uma base valiosa para a GenZ avaliar a sua postura de privacidade. Os objetivos também são úteis para que as empresas de media social e outras plataformas relacionadas elaborem as suas políticas de privacidade de acordo com o que a GenZ deseja. Finalmente, os objetivos são uma ajuda útil para o desenvolvimento de leis e regulamentos; Individual values of GenZ in managing their Internet Privacy: a decision analytic assessment Abstract: Online privacy is a growing concern. As individuals and businesses connect, the problem of privacy continues to remain significant. In this thesis, we address three primary questions - What are the individual values of GenZ concerning online privacy? What are the fundamental objectives of GenZ in terms of protecting their online privacy? What are the means objectives GenZ consider for protecting their online privacy? We argue that online privacy for GenZ is vital to protect. We also argue that protection can be ensured if we understand and know what privacy-related values behold GenZ and define their objectives accordingly. Our research brings the importance of individual values to be central to any discussion of privacy concerns. Values have an essential place in scientific discourse. We note that the concept of values is one of the very few discussed and employed across several social science disciplines. To that effect, in this research, we present value-based objectives for GenZ internet privacy. The objectives are classified into two categories – the fundamental objectives and the means to achieve them. In a final synthesis, our six fundamental objectives guide the management of GenZ Internet Privacy Concerns. The objectives are: Increase trust in online interactions; Maximize responsibility of data custodians; Maximize right to be left alone; Maximize individual ability to manage privacy controls; Maximize awareness of platform functionality; Ensure that personal data does not change. Collectively our fundamental and means objectives are a valuable basis for GenZ to evaluate their privacy posture. The objectives are also helpful for the social media companies and other related platforms to design their privacy policies according to the way GenZ wants. Finally, the objectives are a helpful policy aid for developing laws and regulations.